2018
DOI: 10.1089/brain.2018.0609
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Fluctuations Around Stable Attractor Dynamics Extracted from Highly Nonstationary Electroencephalographic Recordings

Abstract: Since the discovery of electrical activity of the brain, electroencephalographic (EEG) recordings constitute one of the most popular techniques of brain research. However, EEG signals are highly nonstationary and one should expect that averages of the cross-correlation coefficient, which may take positive and negative values with equal probability, (almost) vanish when estimated over long data segments. Instead, we found that the average zero-lag cross-correlation matrix estimated with a running window over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 81 publications
6
18
0
Order By: Relevance
“…The nonlinear excess interrelation patterns (i.e., mutual information matrices corrected using multivariate IAAFT surrogates) on the other hand were patient specific (Figure b). Our observation for the linear interrelations is consistent with recent scalp EEG findings where a generic and very stable background pattern has been found (Müller, Rummel, Goodfellow, & Schindler, ; Olguín‐Rodríguez et al, ). We interpret this as an indication that the linear interrelations mainly reflect the mesiotemporal anatomy, which in our study was recorded in a standardized fashion.…”
Section: Summary and Discussionsupporting
confidence: 92%
“…The nonlinear excess interrelation patterns (i.e., mutual information matrices corrected using multivariate IAAFT surrogates) on the other hand were patient specific (Figure b). Our observation for the linear interrelations is consistent with recent scalp EEG findings where a generic and very stable background pattern has been found (Müller, Rummel, Goodfellow, & Schindler, ; Olguín‐Rodríguez et al, ). We interpret this as an indication that the linear interrelations mainly reflect the mesiotemporal anatomy, which in our study was recorded in a standardized fashion.…”
Section: Summary and Discussionsupporting
confidence: 92%
“…In a previous study [55], we observed fluctuations in the scaling of neural activity in a spontaneously active brain circuit. Olguin-Rodriguez et al have investigated characteristic fluctuations around stable attractor dynamics extracted from highly nonstationary EEG recordings [56]. On the other hand, researchers have demonstrated that the dynamical regime of the sensory cortex converges to stable dynamics around a single stimulus-tuned attractor [57].…”
Section: Discussionmentioning
confidence: 99%
“…At each time step the median R M of all EEG-channels ( M ) is taken as a reference. Hence, for the scheme of 19 electrodes, only one scalp electrode is used as a reference point, but it may change at any instant (Müller et al, 2011, 2014; Olguín-Rodríguez et al, 2018). eqnarrayright center leftRRM…”
Section: Methodsmentioning
confidence: 99%